Biocompatibility natural effect of rhamnolipids in bioremediation process on different biological systems at the site of contamination. Issue 3 (2nd October 2018) - Bharali, Pranjal; Das, S.; Ray, Angana; Pradeep Singh, Salam; Bora, Utpal; Kumar Konwar, Bolin; Singh, Chingakham Brajakishor; Sahoo, Dinabandhu
Abstract: Rhamnolipid is known for its potential for degradation of various harmful and toxic contaminants. However, there is a lack of reports of their effects on different biological systems. Hence, the present study focuses on the assessment of rhamnolipid mixture for their biocompatibility nature. The in vitro and in vivo toxicity studies on the mouse fibroblast cell line (L929) and rabbit skin surface respectively showed that the crude rhamnolipid mixture exhibits a nontoxic behavior ( p < 0.05). Similar results were observed with Aedesalbo pictus larvae. However, studies on monocotyledonous and dicotyledonous seeds showed the toxic behavior of rhamnolipids above their critical micelle concentration values (5–200 mg.L − 1). The antimicrobial property with respect to bacteria was found to be more prominent toward Gram positive (0.5 ± 0.5 mg.L − 1) compared to Gram negative bacteria (2.0 ± 0.7 mg.L − 1) and it was least in case of fungi (2.0 ± 0.2 mg.L − 1). The present study opens up a possibility to study the effects of rhamnolipids on the flora and fauna existing at the site of their application to ensure that it effectively remediates the environment without causing any harm to the on-site living systems. Graphical Abstract: